The TOD suitability index establishing a developmental framework for Transit-Oriented Developments (TOD) - Mogul, Angelo Paulo A. (College of Architecture, University of the Philippines Diliman, 2018)
A transit-oriented development (TOD) uses a planning and design strategy that ensures urban development around transit stations is compact, user-friendly, suitably dense, responsive and mixed-use. It integrates various areas for economic growth and pleasurable travel experience, while protecting and conserving the environment. The concept has been applied in diverse ways such as in pre-developed land (Marina Bay, Singapore), existing transportation nodes (king's Cross, London), and previously industrial land-use areas (Malmo, Sweden), among others. One notable case is that of Hong Kong where various areas were transformed into TODs -- a process that decentralized and distributed places of work and residences into multiple locations, rather than in one general area, as currently experienced in Metro Manila. Planning considers multiple levels of assessment and evaluation. Given the complexity and uniqueness of potential TOD sites, a methodology focused on determining suitability for this type of development must be developed to guide city planners, policy makers, designers, target users and other stakeholders. A World Bank study that looked at various TODs in several countries describes the characteristics of effective TODs. This study provides a sound basis for the development of the methodology that includes all the elements essential in planning and designing appropriate and sustainable TODs that are socially and ecologically effective. The result, a TSI assessment framework, will facilitate discussions during public consultations to address social acceptability issues, and help in reaching development planning decisions among the various interest groups and stakeholders.